On the Co-Existence of Cooperative Principle and Politeness Principle - Wenting, Li (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2017)
In the field of pragmatics, controversies arouses all the time between Cooperative principle and Politeness principle. Some believe Cooperative principle (CP) should be universally accepted, without considering of Politeness principle (PP) while others argue that PP should be taken as the first principle in social interactions. However, the author states in this paper that both CP and PP are significant in daily communication. They can co-exist and should cooperate with each other in guiding people?s utterances in different level, especially in different cultures. This paper tries to illustrate clearly the superiorities and limitations of CP and PP. The analysis serves the next part in which the author explains the feasibility and must for the two principles to co-exist by comparing and case study. And thus, the author finallyconcludes that CP and PP can co-exist and should cooperate for better communication among cultures. Throughout the whole paper, the author not only provides arguments and detailed analysis, but also makes comparison by using examples and detailed contexts to prove her statement. Thus, the explanation and argumentation become reasonable, logical and vigorous. By presenting this paper, the author is going to provide a complete understanding of CP and PP, analyzing them and comparing them with each other. Also, by demonstrating the different level of usage for CP and PP, the author emphasizes the importance for the two to cooperate, especially under different cultural backgrounds. In the way, she hopes that daily communications among people would be easier and more successful.